INTERPRETASI BASIS DATA DENGAN PENDEKATAN TABULASI SILANG UNTUK PEMETAAN DIAGRAM VENN - Nurfidah Dwitiyanti; Erlin Windia Ambarsari; Nunu Kustian (Lembaga Pengembangan Kinerja Dosen, 2022)
Venn diagrams group data sets based on relations, either in the form of combined or slice sets. Venn Diagram mapping occurs when there are interrelated data sets. Weaknesses Venn diagrams do not show interconnected data, such as how many data records come from sorting Query data. In this study, cross-tabulation supports indicating related data in the database, making a Venn Diagram. This research uses cross-tabulation results to facilitate Venn Diagram mapping in database exploration. The variable used as experimental material is student test scores. Database interpretation has evidenced cross-tabulation to map Venn Diagram by separating Grade levels. The breakdown of Grade levels makes it easier to understand the visualization of data in the Venn Diagram. Merging Assignments, UTS, and UAS workable if they have the same goal, referring to the Grade as the data centre. The results obtained that the Grade value with the highest achievement is A-. Assignments worth >= 81.5 by 41%, UTS between values ​​of 73-85.5 by 21%, and UAS between values ​​of 77.5-82.5 by 24%.